Allegorical and Pamphlet Rhetoric in Petko R. Slaveykov’s Verse Fables and Journalistic Works - Andriana Spassova (Zeszyty Cyrylo-Metodiańskie)
The article examines the role of verse fables by Petko R. Slaveykov (1827–1895) in the emergence and development of original literary fables during the Bulgarian National Revival period. It also explores Slaveykov’s journalistic practices and their alignment with contemporary linguistic and ideological trends, reflecting the influence of European thought at the time. Slaveykov’s fables not only conveyed moral principles and Enlightenment ideals but also helped establish an aesthetic foundation for national revivalist education. A significant portion of the article is dedicated to analyzing the allegorical imagery in the humorous-satirical aspects of Slaveykov’s early journalistic work, especially in the newspaper ‘Gayda’ (1863). The analysis includes columns like ‘Greek-Bulgarian Affairs’, ‘Greek Affairs’, and ‘Political View’, highlighting the use of allegorical and pamphleteering rhetoric by Slaveykov as editor-in-chief. Slaveykov skillfully employs figurative language as a strategic tool to engage readers and amplify his messages. His critical and satirical stance targets not only other contemporary periodicals and their editors but, more prominently, the Patriarchate of Constantinople, Greek publications, and supporters of Greek national ideology. In conclusion, the article raises questions about how allegorical language evolved into a form of journalistic jargon, taking on the additional function of serving as a political corrective. Original title in Bulgarian: Алегоричен и памфлетен изказ в басните и публицистиката на Петко Р. Славейков.